2021
DOI: 10.1590/1678-4324-2021210262
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of the Association of IGF-I and IGFALS Genes with Growth Traits in Hamdani Sheep

Abstract: IGF-I and IGFALS play a vital stimulator role in skeletal growth, cell differentiation, metabolism, and other physiological processes. A total of 65 (male and female) animals were used in the study. Animals were measured for growth traits at birth weight, weaning weight, and weights at 6 months. The average daily gain (ADG) was calculated from birth to weaning (ADG1) and from birth to 6th month (ADG2). PCR-RFLP analysis was used to detect IGF-I polymorphism at the 5' regulatory region and IGFALS at Exon 1. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The results of the study were in agreement with a number of studies in this field, as (Thomas et al, 2017) indicated in a study on two Indian goats that the insulinlike growth factor (IGF-1) gene is a member of the somatic axis and plays a major role in cell proliferation and differentiation in the growth of The fetus as well as postnatal growth, where it was significantly (P<0.05) superior to the individuals carrying the genotype GG (31.86 kg) in WWT compared to the individuals carrying the genotype AG (29.56 kg) in the Attappady Blak breed, and it did not show significant differences in WWT in Malabari breed. As well as what Bayraktar et al ( 2021) reported, where there were significant (p < 0.05) differences in WWT in the Iraqi Hamdania sheep breed, where the genotypes AA and BB gave a higher WWT (23.72 and 23.59 kg) respectively compared with the genotype AB (22.98) kg. While there were no significant differences in WG between the three genotypes (BB, AB, AA).…”
Section: Relationship Of the Polymorphism Of 5-utr Of Igf-1 Gene To I...supporting
confidence: 87%
“…The results of the study were in agreement with a number of studies in this field, as (Thomas et al, 2017) indicated in a study on two Indian goats that the insulinlike growth factor (IGF-1) gene is a member of the somatic axis and plays a major role in cell proliferation and differentiation in the growth of The fetus as well as postnatal growth, where it was significantly (P<0.05) superior to the individuals carrying the genotype GG (31.86 kg) in WWT compared to the individuals carrying the genotype AG (29.56 kg) in the Attappady Blak breed, and it did not show significant differences in WWT in Malabari breed. As well as what Bayraktar et al ( 2021) reported, where there were significant (p < 0.05) differences in WWT in the Iraqi Hamdania sheep breed, where the genotypes AA and BB gave a higher WWT (23.72 and 23.59 kg) respectively compared with the genotype AB (22.98) kg. While there were no significant differences in WG between the three genotypes (BB, AB, AA).…”
Section: Relationship Of the Polymorphism Of 5-utr Of Igf-1 Gene To I...supporting
confidence: 87%
“…A distinction must be made between true growth and fattening because true growth includes increasing the animal's size from structural tissues such as muscles and bones. In contrast, fattening increases size caused by increased fatty tissue (Bayraktar and Shoshin, 2022b;Jo et al, 2009). With the development of molecular techniques, it has become possible to identify genes that directly or indirectly affect the growth characteristics of animals (Bayraktar and Shoshin, 2022c;Park et al, 2018).…”
Section: Introductionmentioning
confidence: 99%